The Fifth Evaluation Report on Working Of Community Development and N.E.S. Blocks - Planning Commission (Planning Commission, 1958)
This is the fifth Evaluation Report. It is based upon four elaborate field enquiries into the organisation and operation of the community development and the N.E.S. programmes, the organisation and working of the panchayats, the dissemination of improved agricultural practices and the growth of people’s participation and, finally, the maintenance of records in the development blocks. the emphasis has been on a relatively intensive study of a few selected topics rather than an extensive review of all aspects of the programme. What the study may have lost in comprehensiveness, it has, it is hoped, gained in depth. To the reader, the data and the analysis should be as important as the conclusions reached. During the year there has been a critical examination of the programme and of its relationship with the wider aspects of development and administration. the Fourth Evaluation Report of the P.E.O. was followed by the Report of the COPP Team, which made a number of important recommendations for the reorientation of the .*programme the Programme Evaluation Organisation assisted the COPP Team by undertaking a number of special studies. the major recommendation of the Team was for democratic decentralisation, i.e. transfer of the responsibility for planning and execution of the programme by the representatives of the rural population. the States have accepted the recommendation of the Team in principle, though in applying it to their different conditions, they may adopt different patterns of organisation. Moreover, following the report of the Team, significant changes have been made in the pattern, finance and pace of expansion of the development programme. Development blocks conforming to a single pattern and with a five-year phase are to take the place of the Community Development (C. D.) and National Extension Service (N.E.S.) blocks ; the three-year post-intensive phase is to be replaced by a five-year phase with much greater resources; and finally, the date by which the country is to be completely covered with development blocks has been put off by two years.
Evaluation Report
Government of India